Static electricity - Safetycare Australia (Australia : Safetycare Australia Pty Ltd., 2006)
This program aims to increase people's awareness of static electricity and its potential to result in serious accidents and injuries
A skills education program
Title from title screen
VCD format
Keywords: Electricity -- Industrial applications -- Safety measures; Electrostatics -- Industrial applications -- Safety measures